O ensino e aprendizagem do sistema cardiovascular para estudantes com deficiência visual: recursos didáticos e possibilidades - Cardoso, Iara Maria Dâmaso (2023)
This qualitative research aimed to promote the inclusion of students with visual impairments (VI) in the teaching of the Science subject, specifically in the context of the human cardiovascular system content. To achieve this, we conducted a search within the BDTD (Brazilian Digital Library of Theses and Dissertations) for theses and dissertations addressing this theme and developed educational materials. The research addresses the challenge that teachers may face in creating specific plans for including students with VI and the difficulties these students may encounter in their learning process. Thus, the justification for this research arises from the need to provide supportive educational materials that assist teachers in their work and enhance the learning experience of students with VI.The methodology employed is a qualitative approach based on the relevant theoretical framework related to the research topic. The Educational Product resulting from this research is a digital book with audio descriptions of the human cardiovascular system, specifically tailored to the content taught in Middle School, more specifically in the 8th grade, in alignment with the National Common Core Curriculum (BNCC). The research findings revealed a shortage of studies related to the development of educational resources for teaching science to students with VI. Students with VI emphasized the need for materials with audio descriptions and larger text boxes in their validation, to facilitate better content comprehension. Elementary school teachers evaluated the Educational Product and provided contributions for improvement, showcasing alternative uses, both for sighted students and in conjunction with anatomical models, enriching and augmenting the material. A higher education teacher offered suggestions for modifying the heart illustration featured in the Educational Product, proposing adjustments to both the image and its explanation. The validation of the educational product, titled 'Digital Book of the Cardiovascular System with Audio Description,' proved positive, both by teachers and students with VI. Nevertheless, according to the analyses, there is a need for structural adjustments in the digital book to better suit the target audience of this research. We suggest that further research be conducted to address the absence of educational resources.